International Investment Patterns - Lane, Philip (IMF Working Papers; Working Paper ;, 2004)
The paper provides a systematic analysis of bilateral, source and host factors driving portfolio equity investment across countries, using newly-released data on international equity holdings at the end of 2001. It develops a model that links bilateral equity holdings to bilateral trade in goods and services and finds that the data strongly support such a correlation. Larger bilateral positions are also associated with proxies for informational proximity. It further documents that the scale of aggregate foreign equity asset and liability holdings is larger for richer countries and countries with more developed stock markets.